Makna Simbolik Bale dalam Ritual Keagamaan Melayu Muslim Tanjungbalai: Studi Fenomenologis - Ramli Ramadhan; Neila Susanti; Ismail Marzuki (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study investigates the symbolic meanings of bale in Malay Muslim family rituals in Tanjungbalai and how they sustain social cohesion. Despite its ubiquity, prior research rarely maps the moral grammar of bale, traces intergenerational transmission, or specifies the minimum etiquette that legitimizes recent variations. Using a qualitative phenomenological cultural design, we collected data through nonparticipant observation at khataman, aqiqah, and upah upah; in depth semi structured interviews with religious leaders, adat figures, artisans and organizers, and household members; and document review. The researcher served as the primary instrument. Thematic analysis consisted of iterative coding, theme development, and verification, supported by triangulation, member checking, and an audit trail to ensure trustworthiness. Findings show that bale functions as a value laden sign system rather than ornamentation. Core elements include pulut, egg, inti made from coconut and palm sugar, meat, cover or symmetry, and tiered placement; together they index gratitude, adab, solidarity, sacrifice, and orderly conduct. Although forms vary by event and family preference, the aims of gratitude, etiquette, and silaturahim remain stable. Modernization introduces looser color palettes and occasional uncovered bale, which are accepted when minimum etiquette and communal legitimacy are preserved. Youth knowledge is shaped by family practice and by guidance from religious and adat authorities. The study specifies simple etiquette thresholds and practical supports—concise documentation, intergenerational education, and local leadership—to sustain bale as a medium for transmitting Islamic Malay values and strengthening social bonds.